Clinically relevant outcome measures for new therapies of asthma using pharmaceutical and biologic agents. Issue 3 (June 2015) - Boulet, Louis-Philippe; Chanez, Pascal
<x xml:space="preserve">Abstract</x> Purpose of review To determine the benefits of new asthma drugs or therapies, they should be assessed with regard to their effects on relevant clinical outcomes. Recent findings The most frequently used outcomes have been symptoms, rescue medication needs and pulmonary function tests, although others such as quality of life, exacerbations and impairment of activities have also been identified as important ones. Improvements in our understanding of basic mechanisms of asthma have led to the development of new sets of outcomes including inflammatory markers and a rapidly increasing number of biomarkers, which however require validation, and assessment of their clinical usefulness. Many studies have not only looked at induced sputum cell differentials or FENO to phenotype asthma but also as treatment efficacy markers. Periostin is considered a marker of TH2-induced airway inflammation and a predictor of response to drugs such as anti-IL13 and omalizumab, although at the individual level, such prediction remains imperfect. Summary There is a need to develop new markers of activity of the disease, with a prognostic value with regard to the benefits of new treatments.